THE USE OF INFORMATION TECHNOLOGIES IN PROFESSIONAL TRAINING OF FUTURE DESIGN AND ART SPECIALISTS - Savchenko, Larysa; Kulinka, Julia; Kovalenko, Viktoriia; Valentynivna , Nadiia; Oleksandrivna , Tetiana (Revista Inclusiones, 2020)
Nowadays we pay special attention to the pedagogical technologies which integrate with some information and communication technologies. The last ones contribute to the formation of creative thinking, the ability to operate information using the development of communicative skills. They expand students’ self-education. The article presents some arguments for the information technology and the state of implementation into the system of higher education while teaching design disciplines. The reasonable means of IT penetration, which are used in the education, allow us to realize the main rule of the humanitarian direction in the educational system. They are the transition from the memorizing process to the perception process as the result of mental development; from the purely associative, statistical model of knowledge to the dynamically structured systems of mental actions. The students have been forbidden to perform: a creative project "Interiors, restaurant window design", information project "Application of cross-media communication as a means of image developing of a modern higher education institution", design project "Fashion during the pandemic". The use of information educational environment, aimed at students’ gaining experience in design, provides an opportunity to improve the process of forming design competence of the specialist.